PENGARUH KEPRIBADIAN EKSTROVERT DAN INTROVERT TERHADAP PEMBENTUKAN KARAKTER SOSIAL PADA SISWA - Suriani Darli; Donny Charles Chandra (Bethel Press, 2022)
This study aims to analyze the influence of extrovert and introvert personality types on the development of students’ social character in a junior high school in Banyuwangi Regency, Indonesia. A descriptive qualitative approach was employed, using in-depth interviews, participatory observation, and document analysis for data collection. The findings reveal that extroverted students tend to develop their social character through collaborative activities, leadership roles, and public interactions, while introverted students progress through reflective activities, personal mentoring, and participation in small groups. The process of social character formation in the school is influenced by the interaction among students’ personality traits, school culture, and teachers’ guidance strategies. These findings highlight the importance of applying a fit-to-trait approach tailored to students’ personality characteristics to enhance the effectiveness of social character development programs.